LAND REDISTRIBUTION OF THE OBJECT LANDREFORM IN SUPPORT PROGRAM REFORMA AGRARIAAGRARIAN REFORM PROGRAMME IN THE DISTRICT SUMBAWA - SH, Sapriadi, (Jurnal IUS, 2015)
This study aimed is to analyze the State Land Redistribution of land reform places in Sumbawa. Legal issues that arose in this research are How will is the regulation ofÂ landreform in Indonesia in accordance with the Basic Agrarian Law No. 5 of 1960 and Law No. 56 Year 1960 jo Government Regulation No. 224 of 1961, whether the Act is still relevant implemented and how its implementation in the field today. This study is a normative legal empirical research based on the consideration that it originated from the analysis of the implementation of the redistribution of land by the Government (BPN) in Sumbawa where land reform is made the object belongs to the people themselves who ruled for a long time and worked hereditary. The approaches used are statue approach of legislation, conceptual approaches, analytical approach and the approach sociological approach. The legal materials Data analysed with techniques and legal materials in a systematic way in which the data that have been collected are then analyzed by qualitatively descriptive way to explain, describe, and analyzed existing data on the implementation of land redistribution and land reform object associated with the study of literature that consists of data in the form of documents that have been collected. Based on the results of this study concluded, that the setting of land reform in Indonesia is quite adequate, but the implementation of the program turned out to be having some problems. Basically these obstacles are political, especially relating to the situation of political life, as it also in the New Order era a change-oriented development strategy on growth development. In this case even though the provisions of the land reform is still valid but the implementation has not correspond to the actual desired, besides the vague legal norms in interpreting the regulations implementing land redistribution of object land reform because the mechanisms and procedures in defining landsÂ made the object of reform is not appropriate with Government Regulation Number 224 in 1961. Thus the object of state land redistribution reform in Sumbawa ineffective in practice. practice ineffectivelyKeywords: Land reform is land for farmers.